(untitled) (Eurasian Medical Research Periodical, 2023)
PCOS is a syndrome of ovarian dysfunction that is characterized by the presence of cardinal features of hyperandrogenism and polycystic ovary morphology. Clinical or biochemical hyperandrogenism (HA), ovulatory dysfunction (OD), and/or polycystic ovarian morphology (PCOM) are the three criteria that have been used to characterize PCOS since the creation of the Rotterdam Consensus in 2003, PCOS presence of at least two out of three criteria. This definition results in several PCOS phenotypes, such as phenotype A (ha, od, PCOM), phenotype B (HA, OD), phenotype C (HA, PCOM), and phenotype D (OD, PCOM). Research on adipokines that play roles in metabolic regulation has recently gained interest. This review is a part of the masterwork which would focus on neudesin, and neuregulin_4 and investigate their role as biomarkers for insulin resistance in females affected by PCOS phenotypes